A meta-analytic review of gender composition influencing employees' work outcomes: implications for human resource development. Issue 5 (19th October 2020) - Cheung, HoKwan; Goldberg, Caren B.; Konrad, Alison M.; Lindsey, Alex; Nicolaides, Vias; Yang, Yang
ABSTRACT: Drawing from Kanter's tokenism theory, the current meta-analysis provides a statistical synthesis of the research linking gender composition of the workplace to men and women's evaluative (leadership, rewards, and performance) and affective (interpersonal relationships, stress, and attitudes towards women) outcomes. In addition, we examine the moderating effect of task gender-type on these relationships. Evidence for simple gender composition effects was weak, with only men's interpersonal outcomes being associated with gender composition. In contrast, we found strong evidence supporting the moderating effect of task gender-type on these relationships for both sexes, across several of the outcomes. Notably, the strongest moderator effect was shown for men's leadership, with a clear pattern demonstrating that gender composition has a stronger positive effect on this outcome for men performing gender-neutral tasks, compared to men performing masculine tasks. This underscores the importance of task gender-type as a more powerful indicator of workplace gender norms than a numerical representation of men and women. Despite progress towards gender parity in the workplace, gender hegemony remains strong in male-typed tasks as they stand impervious to the effects of gender composition. Results are discussed in light of tokenism theory and its implications on designs of HRD interventions.